Variation between Pathological Measurement and Endoscopically Estimated Size of Colonic Polyps - Atalaia-Martins,Catarina (2019)
Background and Aims: Accurate determination of colonic polyp size is vital to an appropriate surveillance. The main aim of this study was to evaluate variation between the polyp size reported by the endoscopist and its pathological measurement. Methods: A retrospective analysis of all colonic adenomatous polyps resected in a 12-month period was performed at our center. Endoscopic and pathological size for each polyp were compared, and overestimation rates, underestimation rates, and endoscopic-pathological variation (EPV) were calculated. Results: Among the 573 polyps that were included, the mean endoscopic and pathological sizes were 8.00 and 6.66 mm, respectively. The most frequent error, in 62.1%, was overestimation by the colonoscopist. Overestimation and EPV were associated with resection technique (higher in endoscopic mucosal resection and smaller with biopsy forceps) and colonoscopist. They were not associated with years of experience in colonoscopy. Overestimation was more frequent in larger polyps. Conclusions: Our study shows significant discordance between endoscopic and pathological size of colonic polyps with a clear tendency for endoscopic overestimation. Larger polyps are more difficult to accurately assess than smaller ones. This propensity for error was not related to colonoscopists years of experience and seems to be an individual tendency.